Analisis Faktor Yang Mempengaruhi Pendapatan Pedagang Kaki Lima Malioboro Pasca Relokasi Ke Teras 1 Dan 2 Malioboro Yogyakarta - Rozzaaq, Adhim Nuur; Yuniarti, Dini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
A street vendor is someone who sells on the side of the road and is always found in big cities, especially tourist cities like Yogyakarta. The large number of street vendors on the edge of Jalan Malioboro is a concern for the local government. Relocation has also become a policy carried out by the government to organize the city of Yogyakarta. There are many pros and cons to the relocation policy for Malioboro street vendors, and the average street vendor even holds a demonstration against the relocation. However, in the end this relocation policy continued to work. The street vendors in Malioboro were also relocated to Teras 1 and Teras 2. From this case study research will be carried out regarding the analysis of factors that influence the income of street vendors in Malioboro after relocation. The aim of this research is to find out whether location, working hours, length of business, and type of goods influence the income of street vendors in Malioboro Yogyakarta after relocating to Teras 1 and Teras 2. The research method used in this research is a quantitative method, the data used is primary data, cross section time type, the location of this research is Teras 1 and Teras 2 Malioboro Yogyakarta. The analytical tool in this research uses multiple linear methods. The research results show that there is a difference in traders' income before relocation and after relocation. Judging from the results of the analysis of the difference between the two averages, the daily income of Malioboro Yogyakarta street vendors after relocation is apparently smaller than before relocation. Apart from that, there is a significant influence between the variables of location, working hours, length of business, and type of goods on income